Factorizing trinomials (1)

x^{2} – 2x – 15 =factorize completely(x + 5)(x + 3) (x – 5)(x + 3) (x – 5)(x – 3) (x + 5)(x – 3) x^{2} + 13x + 30 =factorize completely(x + 3)(x + 10) (x – 3)(x + 10) (x – 3)(x – 10) (x + 3)(x – 10) x^{2} – 7x + 12=factorize completely(x + 4)(x + 3) (x – 4)(x + 3) (x – 4)(x – 3) (x + 4)(x – 3) x^{2} + x – 20 =factorize completely(x + 5)(x + 4) (x – 5)(x + 4) (x – 5)(x – 4) (x + 5)(x – 4) x^{2} +4 x – 12 =factorize completely(x + 2)(x + 6) (x – 3)(x + 4) (x – 6)(x – 2) (x + 6)(x – 2) 3x^{2} + 5x – 12 =factorize completely(3x – 3)(x + 4) (3x – 4)(x + 3) (3x + 3)(x – 4) (3x + 4)(x – 3) 3x^{2} + 11x + 10 =factorize completely(3x +5 )(x + 2) (3x -5 )(x + 2) (3x -5 )(x - 2) (3x +5 )(x - 2) 2𝑥^{2} + 13𝑥 − 24 =factorize completely(2x – 3)(x + 4) (2x – 4)(x + 3) (2x - 3)(x + 8) (2x + 4)(x – 3) 2𝑥^{2} − 13𝑥 − 24 =factorize completely(x – 8)(2x + 3) (x – 8)(2x - 3) (x + 8)(2x + 3) (x + 8)(2x - 3) 2y^{2} + 11y + 12 =factorize completely(2y - 3)(y - 4) (2y + 3)(y - 4) (2y - 3)(y + 4) (2y + 3)(y + 4) |

Students who took this test also took :

Created with That Quiz —
a math test site for students of all grade levels.